Effectiveness of physiotherapeutic techniques in urinary incontinence: a review of the literature - Wójcik, Agata; Lamch, Magdalena; Błasik, Natalia; Jabłońska, Monika; Tomys, Julia; Strugała , Urszula; Kędziora–Kornatowska, Kornelia (Journal of Education, Health and Sport, 2022)
Introduction and purpose : Urinary incontinence is a common condition characterized by involuntary urine leakage from urethra. It particularly affects elderly women and is a serious medical, social and economic problem. As a result of recently observed population ageing, the incidence of this anomaly is expected to rise. Due to multifactorial etiology, several types of incontinence are distinguished. Proper diagnostic procedures lead to diagnosis confirmation and allow appropriate therapeutic intervention. Both conservative and surgical methods are used in management of urine incontinence. In addition to pharmacological therapy, physiotherapeutic methods have an important meaning in conservative approach. The aim of this article is a review presenting the results of recent studies on the effectiveness of physiotherapy procedures in treatment of various types of urine incontinence. Description of the state of knowledge: In the study 33 articles which published physiotherapy techniques in 2004-2021 regarding the role of physiotherapeutic methods in the treatment of urinary incontinence were analyzed. The results of studies assessing the effectiveness of physiotherapy techniques (acupuncture, behavioral therapy, yoga, magnetic stimulation, pelvic floor muscle training, vaginal cones, vibration therapy, kinesiotheraphy techniques, stimulation) in reducing the severity of urinary incontinence symptoms and improving the quality of patients’ life were presented on the basis of analyzed literature. Conclusions: Physiotherapy is an effective method of treatment of urinary incontinence and it supports other types of therapy. Therapy should be interdisciplinary approached and the choice of physiotherapeutic methods should be dependent on the individual needs of the patient.